SKIN CAPILLARY ALTERATIONS IN PATIENTS WITH ACUTE SARS-COV-2 INFECTION. (April 2021) - De Ciuceis, Carolina; Rosei, Claudia Agabiti; Brami, Valeria; Rossini, Claudia; Gaggero, Andrea; Fama', Francesca; Muiesan, Maria Lorenza; Rizzoni, Damiano
Abstract : Objective: Acute SarsCoV2 infection is associated with endothelial dysfunction and endothelitis which might explain systemic microvascular impairment. The presence of endothelial damage can promote vasoconstriction with consequent organ ischemia, inflammation, tissue edema and a procoagulant state resulting in an increase in the incidence of cardio- and cerebrovascular events. Microvascular thrombosis has been demonstrated in post-mortem autopsy of COVID19 patients; however no data are available about skin capillary alterations in these patients. Design and method: We evaluated skin microvascular alterations in 14 patients admitted to our hospital with SarsCov2 infection. Basal capillary density was performed by capillaroscopy bedside in the nailfold and in the dorsum of the 4th finger. Results: Fourteen patients (9 males, 5 females) were evaluated: average age was 66 ± 1 years, BMI 26 ± 3. Nine patients were hypertensive (64%), 4 diabetic (29%), 3 were dyslipidemic (21%), 3 with cerebrovascular or cardiovascular disease history (21%). Seven patients were treated with ev steroid (50%), 3 with tocilizumab (21%) and 7 were treated with non-invasive ventilation (50%). During the hospitalisation all patients presented interstitial pneumonia SarsCov2 associated whereas vascular complication (ischaemic stroke or pulmonary embolism) were observed in 3 patients (21%) with SarsCov2 infection. Nine patients showed skin capillary alterations (5 thrombosis, 5 haemorrhage/microbleeding, 4 neoangiogenesis). Interestingly, capillary alterations were present only in patients treated with non-invasive ventilation and/or with cardio- or cerebrovascular complications. These alterations were not detected after 2 month from the discharge. Conclusions: This is the first in vivo evidence of skin capillary thrombosis, microhaemorragia and angiogenesis in patients with acute SARS-CoV2 infection which support the presence of endothelial dysfunction and inflammation. Capillary alterations might reflect systemic vascular effects of viral infection.